A technical analysis of the difference in treatment of technical fees in relation to the receipt of management fees by a resident of South Africa, sourced from Botswana and Zambia, including the impact of domestic and treaty relief - Begg, Nazreen (Department of Finance and Tax, 2020)
With international developments there has over the past few years been an increase in the provision of cross border services. By nature, services are often intangible and can in most cases be provided remotely. As such, an individual or enterprise providing personal services can substantially be involved in another state’s economy without establishing a permanent establishment or fixed base. This phenomenon proved problematic, especially in developing countries who are large importers of services, in that the country paying for the services would not be in a position to tax these activities however would, in terms of application of their domestic laws, be required to provide a deduction in relation to the payment for services where it relates to legitimate costs incurred in the production of income. In light of this, and in an attempt to protect their tax base, it is found that majority of developing countries would incorporate in domestic law a tax on technical services paid to nonresidents. This is usually in the form of a withholding tax. This practice was undesirable for both taxpayers and tax authorities in that it resulted in unrelieved double taxation or double non-taxation which in turn causes difficult disputes whilst consuming scarce resources. In light of this, a new Article 12A- Fees on technical services had been drafted into the 2017 United Nation Double Taxation Convention between Developed and Developing Countries (the “UN Model”). This article provides a Source State to tax certain technical services defined as “any payment in consideration for any service of a managerial, technical or consultancy nature, at a rate agreed between the two States, on a gross basis”. By performing qualitative research, based on a simplistic scenario for management fees, it is found that the inclusion in a treaty of an article similar to Article 12A makes the application of treaty relief easier and neutralises the tax effect for a South African resident. However, where no distributive rules to technical services (in particular management fees) apply in a treaty it may become burdensome to prove that treaty relief should apply in a case where double taxation occurs. Based on the results of the research (due to the economic impact it may have on South Africa), it is recommended that South African treaties with other developing countries which levy a withholding tax on management fees, should be updated by protocol or renegotiation of the treaty to include a similar article to the new Article 12A in the UN Model.